China’s polarizing presence in the developing world: Book review: Yu, H. (2024). Understanding China’s Belt and Road Initiative. Springer. - Delos Santos, Danilo Lorenzo (POLARITIES, 2025)
As the world transitions from the bipolarity of Cold War politics to the hyper-globalized era of the 1980s and 1990s towards the multipolarity of the 2000s, the ossification of political, social, and economic spheres created both opportunities and challenges for the developing world. With the formation of supranational organizations, blocs, and networks, assimilation demands strict rules of conduct and norm adherence that have limited the reach of emerging newly industrializing state actors to capital, expertise, and resources and are subjected to undue pressure to abide. China through its Belt and Road Initiative (BRI) was able to be the developing world’s alternative with its generous packages coupled with lighter requirements but with stipulations that have divided perceptions of its risks. The book Understanding China’s Belt and Road Initiative endeavors to simplify China’s seemingly polarizing BRI program and present an objective take on its impact on the developing world in the status quo.